Stalking Among Domestically Violent Offenders: An Analysis of Police Records - Bendlin, Martyna (Curtin University, 2020)
This thesis investigates coercive control and other forms of violence experienced by stalking victims. The results demonstrate that stalkers use many intrusive behaviours to exert power over victims. Many of these behaviours leave no physical trace on the victim, yet they indicate risk of serious harm. This suggests the importance of accurate recognition of coercively controlling behaviours that may not leave physical injury, yet place victims at high risk of serious physical and psychological damage.